Women’s Language Used in the Video of Counter Strike: Global Offensive Female Player - Satria Wirasa, Komang; Winaya, I Made (Humanis, 2018)
This paper entitled Women Language Used in Video of Counter strike: Global Offensive Female Player. This study aimed at identifying the language features applied by a woman when she played a game entitled Counter Strike: Global Offensive and find out the language style of the utterances in her conversation. The data source of this study was taken from the conversation used by Counter Strike: Global Offensive female players in the video. The collecting data used documenting method and it begins with listen to the conversation in the video and then made a transcript, afterwards, sorted out and categorized the data into women’s linguistic feature and language style. Thereafter, the data analyzed by using quantitative method The findings of this study showed the utterance produced by the female player include sixteen data of women language features and three out of six styles of women language in this video.